2014
DOI: 10.1097/gox.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Deep Cutaneous Wounds Using Dermal Template in Combination with Negative-pressure Therapy and Subsequent Skin Graft

Abstract: Background:We consider the use of dermal matrix associated with a skin graft to cover deep wounds in the extremities when tendon and bone are exposed. The objective of this article was to evaluate the efficacy of covering acute deep wounds through the use of a dermal regeneration template (Integra) associated with vacuum therapy and subsequent skin grafting.Methods:Twenty patients were evaluated prospectively. All of them had acute (up to 3 weeks) deep wounds in the limbs. We consider a deep wound to be that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…An in vitro model by Baldwin et al showed that negative pressure managed to switch endothelial cells, which normally fail to fully penetrate Integra, to a migratory and proliferative phenotype and demonstrated that intermittent negative pressure allowed greatest ingress . Other groups showed significantly increased take rate and integration, reduced hospital stay, improved clinical outcomes, and reduced complication rates when NPWT was applied to Integra . Although cases of hand and upper extremity reconstructions are included in these studies, very few authors have limited their analysis to that anatomical region.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro model by Baldwin et al showed that negative pressure managed to switch endothelial cells, which normally fail to fully penetrate Integra, to a migratory and proliferative phenotype and demonstrated that intermittent negative pressure allowed greatest ingress . Other groups showed significantly increased take rate and integration, reduced hospital stay, improved clinical outcomes, and reduced complication rates when NPWT was applied to Integra . Although cases of hand and upper extremity reconstructions are included in these studies, very few authors have limited their analysis to that anatomical region.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that during the third week after application, blood vessel lumen develops in the template [6]. Studies have also shown a positive association between dermal regeneration templates and negative-pressure therapy by promoting faster integration of the matrix and fewer complications such as infection [7]. This suggests that a combination of INTEGRA ® , negative pressure dressing, and skin graft may favor faster maturation of the dermal template and increase the chance of the graft taking well.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the efficacy of dermal substitutes in reconstructing posttraumatic or post oncological defects, and such techniques now represent a tissue-engineered alternative to flap surgery, especially in medically compromised individuals because they reduce surgical morbidity. 1 , 2 Moreover, dermal substitutes have been investigated even from a functional perspective, and several reports have shown that they might represent a safe and reliable tool for the reconstruction of challenging areas such as joints or weight-bearing surfaces. 3 5 …”
Section: Introductionmentioning
confidence: 99%